The Effect Of Rice Bran Oil And Its Oil Fraction As Shortening Substitute In Bread Production - Eng, Hui Yi (2023)
The study is aimed to study the feasibility of RBO and RBOF as shortening replacer in bread production. In the first phase of this study, the chemical, textural, and thermal properties of CS, RBO, and RBOF were studied and compared. In the second phase study, the rheological, textural, and microstructural properties were determined among dough DS, DO and DF respectively.